Colocalization of Vitiligo and Alopecia Areata: Coincidence or Consequence? - Kumar, Sumir (Medknow Publications & Media Pvt Ltd, 2013)
Both alopecia areata (AA) and vitiligo are autoimmune diseases, and their coexistence in the same patient is not uncommon, as vitiligo has been reported to occur in 4.1% of patients of AA. We present a case of a 15-year-old male child who had vitiligo and later developed AA over the existing lesions of vitiligo over face and scalp and have attempted to elucidate the current understanding of mechanisms of coexistence of these two diseases. Our case lends support to the hypothesis that AA and vitiligo share a common pathogenic pathway including autoimmune response against some common antigens like those derived from the bulb melanocytes. Stimulation of proinflammatory T-helper(Th)-1 cell mediated immunological response or inactivation of a suppressor T-cell mediated response could be the common underlying phenomenon. However, the striking rarity of colocalization of these two diseases has led to the recent debate over current understanding of their pathogenesis, and whether this association is merely a coincidence. As both AA and vitiligo are frequent and chronic dermatological disorders, it is of utmost importance to gain more understanding into their pathogenic mechanisms so that more definitive treatment modalities may be devised and the quality of life of these patients can be improved.